An Overview of Darwinian Literary Studies: A New Science-Based Approach to Literature - Rizano, Gindho; Yeni, Marliza (English Department, Faculty of Humanities, Andalas University, 2022)
This article discusses a newly emerging branch of literary criticism, Darwinian literary studies, an approach with a serious ambition to change the landscape of literary studies. It seeks to outline some of the approach’s key contributions, such as explanations of possible origins of narrative and adaptive functions of literature as well as novel ways of interpreting individual works. This piece of writing also explores the controversies surrounding the approach, namely the stance that the approach takes against the postmodernist establishment and the criticism it receives. Regarding both the main ideas and the controversies, this paper seeks to answer and whether or not this approach is useful or relevant at all in today’s modern world.